2020
DOI: 10.1155/2020/7905380
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Related Prognosis Biomarkers from High-Throughput Sequencing Data of Colorectal Cancer

Abstract: Background. Colorectal cancer (CRC) is the third most common cancer in the world, and most of them are adenocarcinomas. CRC could be classified as colon adenocarcinoma (COAD) and rectum adenocarcinoma (READ) according to the original tumorigenesis position. Increasing evidences indicated that microRNAs (miRNAs) play an important role in the occurrence of multiple tumors. Methods. In this study, we firstly downloaded miRNA (COAD, 8 controls vs. 455 tumors; READ, 3 controls vs. 161 tumors) and mRNA (COAD, 41 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Wang et al [107] identified CACNA1D as part of an 18-ion-channel, prognostic-gene signature in glioma (the direction of the association with survival outcomes was not reported); this finding was observed even though CACNA1D-expression was downregulated in these cells. Xing et al [108] noted that CACNA1D was one of 8 out of 3,747 differentiallyexpressed genes associated with survival outcomes in colon adenocarcinoma: consistent with our findings, those with higher CACNA1D-expression lived longer than those with lower expression [108]. Similar to our metastasis-related findings, CACNA1D was among the 6 genes associated with tumor node metastasis staging in colon adenocarcinoma [108].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Wang et al [107] identified CACNA1D as part of an 18-ion-channel, prognostic-gene signature in glioma (the direction of the association with survival outcomes was not reported); this finding was observed even though CACNA1D-expression was downregulated in these cells. Xing et al [108] noted that CACNA1D was one of 8 out of 3,747 differentiallyexpressed genes associated with survival outcomes in colon adenocarcinoma: consistent with our findings, those with higher CACNA1D-expression lived longer than those with lower expression [108]. Similar to our metastasis-related findings, CACNA1D was among the 6 genes associated with tumor node metastasis staging in colon adenocarcinoma [108].…”
Section: Discussionsupporting
confidence: 91%
“…Xing et al [108] noted that CACNA1D was one of 8 out of 3,747 differentiallyexpressed genes associated with survival outcomes in colon adenocarcinoma: consistent with our findings, those with higher CACNA1D-expression lived longer than those with lower expression [108]. Similar to our metastasis-related findings, CACNA1D was among the 6 genes associated with tumor node metastasis staging in colon adenocarcinoma [108]. Additionally, Fourbon et al [105] showed that colon cancer cell migration was affected by CACNA1D-expression: the migration was decreased when CACNA1D was silenced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 70 miR-NAs are identified by our RNA sequence based signature. In order to ensure the validity of our signature created in this study, we compared to previous miRNA signatures of CRC [23][24][25]. Two miRNAs, miR-592 (upregulated miRNA) and miR-139-5p (downregulated miRNA) were common miRNAs to all four independent signatures (Table S4).…”
Section: Creating Mirna Expression Signature In Crcmentioning
confidence: 99%
“…Due to large changes in lifestyle and dietary habits, the incidence and mortality of CRC will continue to rise. In China, there are 300000 new CRC cases each year, with an annual average increase of 4.2%[ 2 ]. There are obvious gender and regional differences in the incidence and mortality rate of CRC cases, with the overall distribution being more in males than in females, and more in urban areas than in rural areas[ 3 ].…”
Section: Introductionmentioning
confidence: 99%